Illness under the purview of the colonial state demographic inscription of tuberculosis and control efforts in the early American Philippines, 1899-1910 - Moralina, Aaron Rom O. (2010)
This easy elucidates the character of early attempts of the American colonial state to control tuberculosis from 1899 until 1910. It traces the transition from relative neglect, to early attempts to "demographically inscribe" the TB threat, as well as the direct responses deployed to reduce mortality rates from the disease. The easy ends with an exposition of the collective character of the health measures launched by the state, and argues that TB control from 1899 until 1910 comprised a repertoire of interventionist measures aimed, on one hand, to keep in check the pathogenic vector, and, on the other hand, to modify lifestyles and habits viewed to be filthy according to American colonial standards.
Keywords: Tuberculosis -- Early American Philippines, 1899-1910